2014
DOI: 10.1080/01490451.2014.884195
|View full text |Cite
|
Sign up to set email alerts
|

The Up-regulation of Carbonic Anhydrase Genes ofBacillus mucilaginosusunder Soluble Ca2+Deficiency and the Heterologously Expressed Enzyme Promotes Calcite Dissolution

Abstract: Molecular mechanisms and gene regulation are of interest in the area of geomicrobiology in which the interaction between microbes and minerals is studied. This paper focuses on the regulation of the expression of carbonic anhydrase (CA) genes in Bacillus mucilaginosus and the effects of the expression product of the B. mucilaginosus CA gene in Escherichia coli on calcite weathering. Real-time fluorescent quantitative PCR (RT-qPCR) was used to explore the relationship between CA gene expression in B. mucilagino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 66 publications
0
32
1
Order By: Relevance
“…For example, our previous studies showed that bacterial carbonic anhydrase, which is capable of catalysing the reversible hydration reaction, can accelerate mineral weathering [33,34,35]. However, the results of this study did not show the different expression of this particular enzyme.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, our previous studies showed that bacterial carbonic anhydrase, which is capable of catalysing the reversible hydration reaction, can accelerate mineral weathering [33,34,35]. However, the results of this study did not show the different expression of this particular enzyme.…”
Section: Discussioncontrasting
confidence: 55%
“…Another study showed upregulation of CA gene expression in Ca 2+ deficient environments (Xiao et al . ). Thus, the functional variability and the cambialistic nature of CAs could be used as a strategic plan for on‐site CCUS.…”
Section: Carbonic Anhydrasementioning
confidence: 97%
“…A comprehensive analysis indicated that organic and mineral fertilisers can be partially substituted for conventional chemical fertilisers to promote plant growth, improve soil quality, and increase the carbon sink effect in soils (Xiao et al, 2017). The processes are related to the biological weathering effect of microorganisms in soils on potassium-bearing silicate minerals (Xiao et al, 2012b;Xiao et al, 2014; and have been found to be complicated . From the perspective of CA, the mechanism of participation of microorganisms in the biological weathering of silicate minerals and formation of carbon sinks is illustrated in Fig.…”
Section: Increasing Carbon Sink Effects By the Biological Weathering mentioning
confidence: 99%
“…Recent studies have found that the carbonic anhydrase (CA) of microorganisms which can promote the hydration of CO 2 in the atmosphere and is also involved in the biological weathering of silicate minerals and facilitates the formation of carbonate minerals (Xiao et al, 2012b;Sun et al, 2013). The biological weathering of silicate minerals can not only promote the release of mineral elements, but also form a secondary mineral, i.e., a carbonate mineral, thus showing certain carbon sink effects (Xiao et al, 2014;2016a). The current research mainly introduces the potential ecological effects of the biological weathering of silicate minerals, in which the CA of microorganisms participates, and that of utilising the biological weathering of silicate minerals in the fertilisation of farmland.…”
Section: Introductionmentioning
confidence: 99%